Leadership Skills of Undergraduate Students at the Hashemite University and Sultan Qaboos University: Comparative Study - Aieman Ahmad Al-Omari; Yousra Mohammed Al-Mughairi (Ali Khorsandi Taskoh, 2023)
Undergraduate students have identified several skills that should be developed during their college years, such as leadership. A comparative study was conducted to assess the leadership skills of undergraduate students at public universities in Jordan and the Sultanate of Oman. A descriptive method was used, and the S-LPI instrument with five dimensions was applied to the 394 participants in Hu and SQU. The results showed that the students had moderate levels of leadership skills in three dimensions, and female students had a higher degree of leadership skills related to Encouraging the heart than males. No differences in leadership skills between the students' colleges. Students with university clubs' membership have a positive effect on the leadership skills of their members, with all five dimensions being significantly improved. This suggests that students already possess some leadership skills when they enter university, and university administrators should take this into account when creating clubs and encouraging students to join them. The study results enrich the researchers look into how universities can foster an environment where students can develop networking capabilities, and how to collaborate with others in order to achieve their goals.